2019
DOI: 10.21608/zjps.2019.13167.1000
|View full text |Cite
|
Sign up to set email alerts
|

Oleic acid antagonizes the action of high fructose high fat diet on insulin secretion and adipose tissue β-arrestin signaling

Abstract: Insulin resistance is a metabolic disorder associated with a wide array of cardiovascular complications. This study aimed to investigate the effect of oleic acid on a dietary model of insulin resistance in mice using high fructose high fat diet (HFrHFD) focusing on the role of β-arrestin signaling in the adipose tissue. Insulin resistance was induced by feeding mice high fructose high fat diet (HFrHFD) for 16 weeks. Oleic acid (40 mg/kg/day) was orally administered for 4 weeks starting at week 13. At the end o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…Increased pancreatic glucagon secretion would have stimulated the conversion of glycogen in the liver and possibly other storage tissues into glucose, resulting to increased serum glucose levels. In agreement with our results, Ibrahim et al (2019) observed increased fasting blood glucose levels in mice following oleic acid administration. In contrast, dietary consumption of oleic acid-rich oils, like the residual oil of MSC, demonstrated decreased blood and plasma glucose levels in humans and rodents ( Mokuda et al, 1993 ; Rasmussen et al, 1993 ).…”
Section: Discussionsupporting
confidence: 93%
“…Increased pancreatic glucagon secretion would have stimulated the conversion of glycogen in the liver and possibly other storage tissues into glucose, resulting to increased serum glucose levels. In agreement with our results, Ibrahim et al (2019) observed increased fasting blood glucose levels in mice following oleic acid administration. In contrast, dietary consumption of oleic acid-rich oils, like the residual oil of MSC, demonstrated decreased blood and plasma glucose levels in humans and rodents ( Mokuda et al, 1993 ; Rasmussen et al, 1993 ).…”
Section: Discussionsupporting
confidence: 93%